2017
DOI: 10.1158/1078-0432.ccr-16-1562
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compound ARN-3236 Inhibits Salt-Inducible Kinase 2 and Sensitizes Ovarian Cancer Cell Lines and Xenografts to Paclitaxel

Abstract: Purpose SIK2 is a centrosome kinase required for mitotic spindle formation and a potential target for ovarian cancer therapy. Here we examine the effects of a novel small molecule SIK2 inhibitor, ARN-3236, on sensitivity to paclitaxel in ovarian cancer. Experimental Design SIK2 expression was determined in ovarian cancer tissue samples and cell lines. ARN-3236 was tested for its efficiency to inhibit growth and enhance paclitaxel sensitivity in cultures and xenografts of ovarian cancer cell lines. SIK2 siRNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 38 publications
6
82
0
Order By: Relevance
“…Although it is possible that the efficacy of miR‐874‐3p and miR‐874‐5p in inhibiting EOC cell chemoresistance is due to blocking SIK2's maintenance of mitotic spindle formation, further research is necessary to determine the mechanism by which SIK2 overexpression restores EOC tumorigenicity. Because SIK 2 promotes the metastasis of ovarian cancer and the resistance to Paclitaxel treatment, which has been confirmed in our study, SIK2 could be used as a good target for ovarian cancer treatment in the future. Overall, this study represents a great step forward in our identification of clinical biomarkers and personalized treatments for EOC that are necessary to reduce the high morbidity and mortality that patients suffer.…”
Section: Discussionsupporting
confidence: 75%
“…Although it is possible that the efficacy of miR‐874‐3p and miR‐874‐5p in inhibiting EOC cell chemoresistance is due to blocking SIK2's maintenance of mitotic spindle formation, further research is necessary to determine the mechanism by which SIK2 overexpression restores EOC tumorigenicity. Because SIK 2 promotes the metastasis of ovarian cancer and the resistance to Paclitaxel treatment, which has been confirmed in our study, SIK2 could be used as a good target for ovarian cancer treatment in the future. Overall, this study represents a great step forward in our identification of clinical biomarkers and personalized treatments for EOC that are necessary to reduce the high morbidity and mortality that patients suffer.…”
Section: Discussionsupporting
confidence: 75%
“…Broadly, these kinases can regulate cell polarity, migration, and metabolism in specific cell contexts [42]. Salt-inducible kinases SIK2 and SIK3 may be required in HGSOC metastasis, but their dependence on LKB1 in this disease is unknown [43][44][45]. AMPK-related kinase ARK5/NUAK1 has been reported to be overexpressed in EOC and implicated in the regulation of EMT [46].…”
Section: Discussionmentioning
confidence: 99%
“…there was also research [22] which found that inhibiting the expression of SIK2 with a specific inhibitor could enhance the sensitivity of ovarian cancer cells to paclitaxel. All indicate that SIK2 plays a vital part in the chemotherapy resistance of tumors, but this is the first time that we have proved that downregulation of SIK2 expression in BC cells can reverse their resistance to cisplatin.…”
Section: Discussionmentioning
confidence: 99%